Experimental Mathematics. Volume 14, Number 4, 2005 - A K Peters (A K Peters, 2009)
A Partial Order in the Knot Table Full TextPDF (193.1 KB) Authors Teruaki Kitano and Masaaki Suzuki 385-390 On the Congruence ax + by = 1 Modulo xy Full TextPDF (949.0 KB) Authors J. Brzeziński, W. Holsztyński and P. Kurlberg 391-401 Small Limit Points of Mahler's Measure Full TextPDF (262.0 KB) Authors David W. Boyd and Michael J. Mossinghoff 403-414 A Quick and Dirty Irreducibility Test for Multivariate Polynomials over q Full TextPDF (302.6 KB) Authors H. -C.Graf V. Bothmer and F. -O. Schreyer 415-422